AUTONOMOUS DRONE DEVELOPMENT FOR EXPLORATION AND SURVEILLANCE WITH HYBRID COMMUNICATION - Budi Pratama, Satrya
In recent years, many developments have been made in the field of Unmanned Aircraft Systems (UAS), including drones and systems for exploring unknown and dangerous areas, where people can't interact directly. Therefore, we need drones that can fly autonomously with various system integration for doing such a mission quickly safely, accurately, and cheaply. In this thesis, we design ZeroHexa: a hexacopter for exploration and surveillance. It will perform guidance and navigation using simultaneous localization and mapping (SLAM) with Google Cartogpraher and path-planning with A* and DWA based on a Robot Operating System (ROS) with 2-D LiDAR. It provides a reliable connection to the ground control station (GCS) with dual channel 4G long-term evolution (LTE) communication and 433 MHz radio telemetry for data communication which we called hybrid communication. Also, we developed a single-page web application using Next.js for human-robot interface (HRI). In real-world evaluations, we find that ZeroHexa can perform up to 15 minutes of flight time at task exploration unmapped areas with reliable data connection of uplink bandwith 0.23 MBps with latency 168 ms and a downlink bandwidth of 0.82 MBps with latency 36.43 ms. Two cameras are mounted on it for giving front, bottom, and top angle views to provide a live video stream or post-processing that can further be used for computer vision applications. Finally, we analyze the feasibility of the system including flight performance, application acceptance features, and network benchmarking. It shows successful autonomous flight missions in simulation as well as in the real-world scenario. Furthermore, this work can be adapted in some research areas as it covers control, network, software, and computer vision that will be relevant for such development.